Preparation method of far-infrared heating heat-preservation comfortable fiber

By forming Cu2S@CNTs nanocomposites in the fibers, the problem of poor Cu2S dispersion is solved, and the efficient light absorption and heating, far infrared heating and moisture-conducting and breathable properties of the fibers are achieved, thereby improving the overall performance of the fibers.

CN119411246APending Publication Date: 2025-02-11杭州智元研究院有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411627322.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Cu2S has poor dispersion in fibers and is prone to agglomeration to form large particles, affecting the mechanical properties and comfort of the fibers.

Method used

By aminating the carbon nanotubes, the copper ions are adsorbed by their chelation, and Cu2S@CNTs nanocomposites are formed simultaneously through weak reduction. The light absorption characteristics of the carbon tubes are used as the template to load Cu2S, forming high-efficiency light absorption and heating A nanocomposite with far-infrared properties and a star anise hollow fiber is prepared by melt spinning.

Benefits of technology

It realizes uniform dispersion of Cu2S in the fiber, improves the light absorption and heating, far-infrared heating and moisture-conducting and breathable properties of the fiber, and has good mechanical properties, washing resistance and comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411246A_ABST
    Figure CN119411246A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of far-infrared heating thermal-insulation comfortable fibers, which comprises the following steps: aminating carbon nanotubes, dispersing the aminated carbon nanotubes in an aqueous solution, and then adding a copper source and a sulfur source to prepare a Cu2S-CNTs nano composite material; the octagonal hollow fiber is prepared by blending the octagonal hollow fiber with polyethylene glycol terephthalate to prepare a far infrared heating master batch, and blending the master batch with polyethylene glycol terephthalate for spinning. The fiber prepared by the invention has good far infrared heating capability, light absorption heating capability and excellent heat retaining property and comfort, and the prepared fabric has good breaking strength, weaving characteristic and excellent washability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fiber manufacturing technology, and in particular to a method for preparing far-infrared heating and thermal insulation comfort fiber. Background Art

[0002] Current heating textiles generally achieve heating by coating or doping functional materials on the fiber surface. These traditional methods mainly include coating method, composite fiber method and doping method. However, the coating method is simple but has poor durability and affects comfort; the composite fiber method improves durability and comfort but has complex process, high cost and poor dispersion; the doping method improves uniformity but has poor compatibility and is easy to reduce fiber performance.

[0003] At present, the common photothermal materials on the market are mainly inorganic nanomaterials such as copper oxide, iron oxide, carbon nanotubes, graphene, etc., each with different advantages and disadvantages. Inorganic nanomaterials have high photothermal conversion efficiency, but poor dispersion in fibers, easy to aggregate into large particles, affecting the mechanical properties and comfort of fibers. Organic photothermal materials are easier to combine with fibers, but have low photothermal conversion efficiency and poor durability.

[0004] In order to overcome these shortcomings, researchers are committed to developing new photothermal functional materials and preparation methods to improve the photothermal conversion efficiency and durability of fibers. Among them, Cu2S (copper sulfide), as a new photothermal material, shows many unique advantages and advancements such as high photothermal conversion efficiency, good chemical stability and far-infrared emission performance. However, Cu2S has poor dispersion in fibers and is easy to aggregate to form large particles. Summary of the invention

[0005] The present application provides a method for preparing far-infrared heating and thermal insulation comfort fibers, which can be used to solve the problem of poor dispersion of Cu2S in fibers and easy aggregation to form large particles, ensuring that the material has high light absorption and heating performance, thermal insulation performance and good comfort, and has good breaking strength, weaving characteristics and excellent wash resistance.

[0006] A preparation method of far-infrared heat-generating and thermal insulation comfort fiber, wherein carbon nanotubes with excellent light absorption characteristics are subjected to amino modification, and copper ions are adsorbed by the chelation effect thereof, and Cu2S@CNTs nanocomposite materials are simultaneously formed by the weak reduction effect of the amino group thereof, and the light absorption characteristics of the carbon tubes are used as templates to load Cu2S synchronously, and the two synergistically form a nanocomposite material with high-efficiency light absorption, heat generation and far-infrared performance. A high-content masterbatch is prepared by twin-screw melt extrusion granulation to achieve uniform dispersion in a polymer matrix. The fiber cross section is designed by a melt spinning method to prepare an octagonal hollow functional fiber material, which simultaneously has multiple functional characteristics of light absorption, heat generation, far-infrared heat generation and moisture conduction and air permeability.

[0007] Furthermore, the preparation method of the far-infrared heat-insulating comfort fiber specifically comprises the following steps:

[0008] Step 1, preparing aminated carbon nanotubes: dispersing carbon nanotubes in DMF, adding thionyl chloride, and then adding ethylenediamine, and obtaining aminated carbon nanotubes after reaction;

[0009] Step 2, preparing a Cu2S@CNTs nanocomposite material: dispersing the amino-modified carbon nanotubes in water, then adding a copper source, and after the reaction, adding a sulfur source to prepare a Cu2S@CNTs nanocomposite material;

[0010] Step 3, preparation of far-infrared heating, thermal insulation and comfort polyester fiber: Cu2S@CNTs nanocomposite material and polyethylene terephthalate are mixed by twin screw to prepare corresponding masterbatch, and the prepared masterbatch is mixed with PET chips in proportion and then extruded by single screw and octagonal hollow spinneret to prepare octagonal hollow functional fiber.

[0011] Preferably, in step 1, the carbon nanotubes are multi-walled carbon nanotubes with a length of 100-400 nm.

[0012] Preferably, in step 1, the ratio of the carbon nanotubes to DMF, thionyl chloride and ethylenediamine is 1g:100ml:0.05-0.08mol:0.075-0.12mol

[0013] Preferably, in step 2, the ratio of the amino-modified carbon nanotubes to the copper source and the sulfur source is 1g:0.05-0.12mol:0.05-0.12mol; the copper source is one or more of copper chloride, copper sulfate, copper nitrate and copper acetate; the sulfur source is one or more of sodium sulfide, barium sulfide and calcium sulfide.

[0014] Preferably, in step 3, the content of Cu2S@CNTs nanocomposite material in the masterbatch is 25-35wt%.

[0015] Preferably, in step 3, the amount of the masterbatch added is 1-3wt%, and the fiber morphology is octagonal hollow.

[0016] Preferably, in step 3, the fiber fineness is 40-150d, the strength is 2.6-4.0cN / dtex, the temperature rises by 10-25°C under 400-1100nm wavelength light irradiation for 20min, the far-infrared emissivity is 0.93-0.98, the far-infrared radiation temperature rise is 2.2-2.8°C, and the water washability is greater than 50 times.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] Highly efficient light absorption and photothermal conversion efficiency: Carbon nanotubes have excellent light absorption properties, and Cu2S nanomaterials have high photothermal conversion efficiency, which can effectively convert the absorbed light energy into thermal energy to achieve rapid heating.

[0019] Small particle size and high efficiency: By amino-modifying carbon nanotubes, they have good chelating properties for metal particles and can be simultaneously reduced to form cuprous ions. Based on the chelation effect and template loading effect, the preparation of small-particle Cu2S is simultaneously achieved, forming a Cu2S@CNTs nanocomposite material with high efficiency in heat absorption and light absorption and heat generation.

[0020] Uniform dispersion: By preparing Cu2S@CNTs nanocomposite materials, the amount used is very small due to its high efficiency; and because a part of the amino group still remains on the surface of the carbon nanotubes, it is easier to disperse in the polymer matrix, and the prepared fiber material has good mechanical properties and weaving properties.

[0021] Comfortable and multifunctional: Due to the good dispersibility of Cu2S@CNTs nanocomposite materials, octagonal hollow shaped fibers can be prepared, which makes the fibers themselves have excellent thermal insulation and moisture conductivity properties; the introduction of Cu2S@CNTs nanocomposite materials gives them excellent light absorption, heat generation, far infrared and bactericidal capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is an appearance morphology diagram of the octagonal hollow fiber provided in the embodiment of the present application;

[0023] Figure 2 This is a light absorption and heat generation diagram of the far-infrared heat-insulating comfort fiber provided in an embodiment of the present application. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below in conjunction with the accompanying drawings.

[0025] The method of the present application comprises: step S1, dispersing the dried carbon nanotubes into dry DMF, dropping an excess of thionyl chloride, heating to 65-70°C for reaction, cooling, adding a large amount of anhydrous THF thereto, centrifuging, collecting the filter residue, repeatedly adding anhydrous THF for washing, vacuum drying to obtain acyl chloride carbon nanotubes, and adding ethylenediamine to obtain amination carbon nanotubes;

[0026] Step S2, dispersing the aminated carbon nanotubes in water at a temperature of 50-65°C, adding a copper source, stirring and reacting for 2-3 hours; then adding a sulfur source, reacting for 3-5 hours, centrifuging and drying to obtain a Cu2S@CNTs nanocomposite material;

[0027] Step S3, the Cu2S@CNTs nanocomposite material and polyethylene terephthalate are mixed by a twin-screw extruder to prepare a corresponding masterbatch, and the functional masterbatch is further mixed with the matrix to prepare an octagonal hollow functional fiber after single-screw extrusion and an octagonal hollow spinneret.

[0028] The present invention adopts the following test methods to test the heating performance, breaking strength and washability:

[0029] Temperature rise performance: Under the conditions of temperature of (20±2)℃ and relative humidity of (65±2)%, use XR-3 light thermal storage performance tester and xenon arc lamp as the irradiation light source. Place the sample under a certain irradiation intensity. The sample absorbs light energy and causes the temperature to change. Use a temperature sensor to test the sample temperature. Record the temperature change of the sample at each time point within 10 minutes of irradiation and 10 minutes of turning off the light source. Calculate the maximum temperature rise value, average temperature rise value and test endpoint temperature rise value of the sample within 20 minutes.

[0030] Breaking strength: Use a tensile testing machine to test the breaking strength of high-efficiency photothermal heating and thermal insulation functional fibers according to ASTM D2256. After conditioning the fiber sample (length 250mm) at a temperature of (20±2)°C and a relative humidity of (65±5)% for 24 hours, clamp it between the clamps of the tensile testing machine, and set the stretching speed to 300mm / min. Start the testing machine and gradually increase the stress until the sample breaks, record the maximum load and elongation at break, and calculate the breaking strength. Repeat the test for at least 10 samples, and calculate the average breaking strength and standard deviation. Finally, generate a test report, record the test conditions, data, and analysis results to evaluate the mechanical properties of the fiber.

[0031] Washability: The high-efficiency photothermal heating and heat preservation functional fiber was tested for 50 washing cycles using a standard washing machine and a phosphorus-free detergent, and the sample was dried after each wash. After every 10 washes, the breaking strength of the sample was tested using a tensile testing machine according to the ASTM D2256 standard, and its photothermal heating performance was evaluated. The test results showed that after 50 washes, the breaking strength and photothermal heating performance of the fiber remained at a high level, indicating that the fiber has good washability.

[0032] Example 1

[0033] (1) Preparation of aminated carbon nanotubes: 1 kg of multi-walled carbon nanotubes with a length of 100 nm were dispersed in 100 L DMF, 80 mol of thionyl chloride was added, the temperature was raised to 70° C., and the reaction was continued for 2 h. Subsequently, 120 mol of ethylenediamine was added, and the aminated carbon nanotubes were obtained after the reaction was continued for 2 h.

[0034] (2) Preparation of Cu2S@CNTs nanocomposite: 1 kg of amino-modified carbon nanotubes was dispersed in 100 L of water, followed by the addition of 120 mol of copper chloride, and then 120 mol of calcium sulfide was added after the reaction at 65 °C. The reaction was continued for 2 h to obtain the Cu2S@CNTs nanocomposite;

[0035] (3) Preparation of far-infrared heat-insulating and comfortable polyester fiber: 350 g of Cu2S@CNTs nanocomposite material and 650 g of polyethylene terephthalate powder were stirred in a high-speed stirring device at a temperature of 85°C and a stirring speed of 1800 r / min for 1 h, and then mixed by a twin-screw extruder at 265°C to prepare a corresponding PET / Cu2S@CNTs masterbatch with a content of 35%. The prepared masterbatch was mixed with PET chips in a ratio of 3:97, and then extruded by a single screw extruder and an octagonal hollow spinneret at 282°C to prepare an octagonal hollow functional fiber, the appearance of which is shown in FIG. Figure 1 As shown, the spinning condition was set at a winding speed of 4500 m / min.

[0036] (4) The prepared octagonal hollow fiber has a specification of 150D / 36F and a strength of 3.0 cN / dtex. After being washed 50 times and irradiated with light for 20 minutes and then heated to 21°C, the antibacterial rate against Escherichia coli, Staphylococcus aureus and Candida albicans was 99.9%. Figure 2 As shown, the far-infrared emissivity is 0.96 and the radiation temperature rise can reach 2.6°C.

[0037] Example 2

[0038] (1) Preparation of aminated carbon nanotubes: 1 kg of multi-walled carbon nanotubes with a length of 400 nm were dispersed in 100 L DMF, 50 mol of thionyl chloride was added, the temperature was raised to 65° C., and the reaction was continued for 2 h. Subsequently, 75 mol of ethylenediamine was added, and the aminated carbon nanotubes were obtained after the reaction was continued for 2 h.

[0039] (2) Preparation of Cu2S@CNTs nanocomposite: 1 kg of amino-modified carbon nanotubes was dispersed in 100 L of water, followed by the addition of 50 mol of copper sulfate, and then 50 mol of barium sulfide was added after the reaction at 65 °C. The reaction was continued for 2 h to obtain the Cu2S@CNTs nanocomposite;

[0040] (3) Preparation of far-infrared heating, thermal insulation and comfort polyester fiber: 250 g of Cu2S@CNTs nanocomposite material and 750 g of polyethylene terephthalate powder were stirred in a high-speed stirring equipment at a temperature of 85°C and a stirring speed of 1800 r / min for 1 h, and then mixed by a twin-screw extruder at 265°C to prepare a corresponding PET / Cu2S@CNTs masterbatch with a content of 25%. The prepared masterbatch was mixed with PET chips in a ratio of 1:99 and then extruded by a single screw extruder and an octagonal hollow spinneret at 282°C to prepare octagonal hollow functional fibers. The spinning conditions were set to a winding speed of 4500 m / min.

[0041] (4) The prepared octagonal hollow fiber has a specification of 40D / 36F and a strength of 2.6 cN / dtex. After being washed 50 times and irradiated with light for 20 minutes, the temperature rises by 11°C. The antibacterial rate against Escherichia coli, Staphylococcus aureus and Candida albicans is 99.2%, the far-infrared emissivity is 0.93, and the radiation temperature rise can reach 2.3°C.

[0042] Example 3

[0043] (1) Preparation of aminated carbon nanotubes: 1 kg of multi-walled carbon nanotubes with a length of 200 nm were dispersed in 100 L DMF, 65 mol of thionyl chloride was added, the temperature was raised to 70° C., and the reaction was performed for 2 h. Subsequently, 100 mol of ethylenediamine was added, and the aminated carbon nanotubes were obtained after the reaction for 2 h.

[0044] (2) Preparation of Cu2S@CNTs nanocomposite: 1 kg of amino-modified carbon nanotubes was dispersed in 100 L of water, followed by the addition of 85 mol of copper nitrate, and then 85 mol of sodium sulfide was added after the reaction at 65 °C. The reaction was continued for 2 h to obtain the Cu2S@CNTs nanocomposite;

[0045] (3) Preparation of far-infrared heating, thermal insulation and comfort polyester fiber: 300 g of Cu2S@CNTs nanocomposite material and 700 g of polyethylene terephthalate powder were stirred in a high-speed stirring equipment at a temperature of 85°C and a stirring speed of 1800 r / min for 1 h, and then mixed by a twin-screw extruder at 265°C to prepare a corresponding PET / Cu2S@CNTs masterbatch with a content of 30%. The prepared masterbatch was mixed with PET chips in a ratio of 2:98 and then extruded by a single screw extruder and an octagonal hollow spinneret at 282°C to prepare octagonal hollow functional fibers. The spinning conditions were set to a winding speed of 4500 m / min.

[0046] (4) The prepared octagonal hollow fiber has a specification of 75D / 36F and a strength of 3.3 cN / dtex. After being washed 50 times and irradiated with light for 20 minutes, the temperature was raised by 23°C. The antibacterial rate against Escherichia coli, Staphylococcus aureus and Candida albicans was 99.5%, the far-infrared emissivity was 0.98, and the radiation temperature rise could reach 2.8°C.

[0047] Example 4

[0048] (1) Preparation of aminated carbon nanotubes: 1 kg of multi-walled carbon nanotubes with a length of 150 nm were dispersed in 100 L DMF, 70 mol of thionyl chloride was added, the temperature was raised to 70° C., and the reaction was carried out for 2 h. Subsequently, 80 mol of ethylenediamine was added, and the reaction was carried out for 2 h to obtain aminated carbon nanotubes;

[0049] (2) Preparation of Cu2S@CNTs nanocomposite: 1 kg of amino-modified carbon nanotubes was dispersed in 100 L of water, followed by the addition of 60 mol of copper acetate, and then 60 mol of sodium sulfide was added after the reaction at 65 °C. The reaction was continued for 2 h to obtain the Cu2S@CNTs nanocomposite;

[0050] (3) Preparation of far-infrared heat-insulating and comfortable polyester fiber: 280 g of Cu2S@CNTs nanocomposite material and 720 g of polyethylene terephthalate powder were stirred in a high-speed stirring device at a temperature of 85°C and a stirring speed of 1800 r / min for 1 h, and then mixed by a twin-screw extruder at 265°C to prepare a PET / Cu2S@CNTs masterbatch with a content of 28%. The prepared masterbatch was mixed with PET chips in a ratio of 2:98, and then extruded by a single screw extruder and an octagonal hollow spinneret at 282°C to prepare an octagonal hollow functional fiber, the appearance of which is shown in FIG. Figure 1 As shown, the spinning condition was set at a winding speed of 4200 m / min.

[0051] (4) The prepared octagonal hollow fiber has a specification of 75D / 48F and a strength of 3.7 cN / dtex. After being washed 50 times and irradiated with light for 20 minutes and then heated to 18°C, the antibacterial rate against Escherichia coli, Staphylococcus aureus and Candida albicans was 99.3%. Figure 2 As shown, the far-infrared emissivity is 0.97 and the radiation temperature rise can reach 2.6°C.

[0052] This method can prepare Cu2S nanocomposites with ultra-small particle size and high dispersion through the template-loaded growth method, which improves its performance and reduces the amount of addition. The synergistic effect of Cu2S and carbon nanotubes greatly improves the light absorption and heat generation capacity and far-infrared capacity. Furthermore, by designing the octagonal hollow morphology, it has the comfort of heat preservation and moisture conduction at the same time.

[0053] The above-described embodiments of the present application do not constitute a limitation on the protection scope of the present application.

Claims

1. A method for preparing far-infrared heating and heat preservation comfort fiber, characterized in that: The following steps are involved: Step S1, dispersing the dried carbon nanotubes into dry DMF, dropping an excess of thionyl chloride, heating to 65-70°C for reaction, cooling, adding anhydrous THF, centrifuging, collecting the filter residue, repeatedly adding anhydrous THF for washing, vacuum drying to obtain acyl chloride carbon nanotubes, and adding ethylenediamine to obtain amination carbon nanotubes; Step S2, dispersing the aminated carbon nanotubes in water at a temperature of 50-65° C., adding a copper source, stirring and reacting for 2-3 hours; then adding a sulfur source, reacting for 3-5 hours, centrifuging and drying to obtain a Cu2S@CNTs nanocomposite material; Step S3, the Cu2S@CNTs nanocomposite material and polyethylene terephthalate are mixed by a twin-screw extruder to prepare a corresponding masterbatch, and the functional masterbatch is further mixed with the matrix to prepare an octagonal hollow functional fiber after single-screw extrusion and an octagonal hollow spinneret.

2. The method for preparing the far-infrared heating and thermal insulation comfort fiber according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with a length of 100-400nm.

3. The method for preparing the far-infrared heating and thermal insulation comfort fiber according to claim 1, characterized in that: The ratio of the carbon nanotubes to DMF, thionyl chloride and ethylenediamine in step S1 is 1 g: 100 ml: 0.05-0.08 mol: 0.075-0.12 mol.

4. The method for preparing the far-infrared heating and thermal insulation comfort fiber according to claim 1, characterized in that: The ratio of the aminated carbon nanotubes to the copper source and the sulfur source in step S2 is 1g:0.05-0.12mol:0.05:0.12mol; the copper source is one or more of copper chloride, copper sulfate, copper nitrate and copper acetate; the sulfur source is one or more of sodium sulfide, barium sulfide and calcium sulfide.

5. The method for preparing the far-infrared heating and thermal insulation comfort fiber according to claim 1, characterized in that: The content of Cu2S@CNTs nanocomposite material in the masterbatch described in step S2 is 25-35wt%.

6. The method for preparing the far-infrared heating and thermal insulation comfort fiber according to claim 5, characterized in that: The addition amount of masterbatch is 1-3wt%, and the fiber morphology is octagonal hollow.